2020
DOI: 10.1111/tpj.15000
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intracellular NAD status affect stomatal development in an abscisic acid‐dependent manner

Abstract: SUMMARY Nicotinamide adenine dinucleotide (NAD) plays a central role in redox metabolism in all domains of life. Additional roles in regulating posttranslational protein modifications and cell signaling implicate NAD as a potential integrator of central metabolism and programs regulating stress responses and development. Here we found that NAD negatively impacts stomatal development in cotyledons of Arabidopsis thaliana. Plants with reduced capacity for NAD+ transport from the cytosol into the mitochondria or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 109 publications
(175 reference statements)
0
21
0
Order By: Relevance
“…Unlike AvrPtoB, HopAM1 and HopF2 act similarly to enhance ABA sensitivity and suppress immune responses for P. syringae virulence, but the underlying biochemical mechanism is not known (de Torres‐Zabala et al ., 2007 ; Goel et al ., 2008 ; Cao et al ., 2019 ). However, recent studies have revealed an unexpected link between NAD + and the ABA response pathway with NAD + regulation probably upstream of ABA signaling (Feitosa‐Araujo et al ., 2020 ; Hong et al ., 2020 ). While endogenous NAD + levels in plant leaves are depleted as a consequence of HopAM1 overexpression via Agrobacterium ‐mediated transformation, NAD + homeostasis is not changed significantly by T3SS‐delivered HopAM1.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike AvrPtoB, HopAM1 and HopF2 act similarly to enhance ABA sensitivity and suppress immune responses for P. syringae virulence, but the underlying biochemical mechanism is not known (de Torres‐Zabala et al ., 2007 ; Goel et al ., 2008 ; Cao et al ., 2019 ). However, recent studies have revealed an unexpected link between NAD + and the ABA response pathway with NAD + regulation probably upstream of ABA signaling (Feitosa‐Araujo et al ., 2020 ; Hong et al ., 2020 ). While endogenous NAD + levels in plant leaves are depleted as a consequence of HopAM1 overexpression via Agrobacterium ‐mediated transformation, NAD + homeostasis is not changed significantly by T3SS‐delivered HopAM1.…”
Section: Discussionmentioning
confidence: 99%
“…NAD(P) + was believed to be a key regulator on energy metabolism and carbon : nitrogen (C : N) balance (Takahashi et al ., 2009). A recent study reported that mutant of NAD + mitochondria transporter ndt1 − :ndt1 − and ndt2 − :ndt2 − displayed the decreased meristemoids number and stomata production (Feitosa‐Araujo et al ., 2020), suggesting the energy homeostasis plays a critical role for stomatal development. Here, we provide several lines of evidence demonstrating that sugar and TOR play the critical roles in the cell proliferation for stomatal development.…”
Section: Discussionmentioning
confidence: 99%
“…It may be linked to ABA, which plays a key role in regulating stomatal movement [ 50 , 51 , 52 ]. Recent studies have shown that the exogenous application of NAD leads to an increase in the ABA content [ 53 ]. At the same time, an increase or decrease in NAD leads to a decrease in plant stomatal number and density, suggesting that NAD may indirectly affect stomatal development by influencing ABA synthesis and signal transduction [ 54 ].…”
Section: Discussionmentioning
confidence: 99%